Penentuan Titik Lokasi Pelabuhan Penyeberangan Amed Di Kabupaten Karangasem - I Gusti Ngurah Putra Dirgayusa (Journal of Marine and Aquatic Sciences, 2016)
Accumulation of social activity, economy and transportation that occur in Southern part of Bali adversely affects at transportation infrastructure carrying activity in this area. These require the government to get the solution of this problem. Through spatial planning area of Bali province 2005, governments establish Amed Bay developed as crossing harbor. These cases mean to divide the shout hem traffic line and support the development in northern part of Bali. The object of this research is in Purwakerti village, district of Abang, Karangasem regency. Research held based on technical and legality review. In advance analyze of those aspects that established some alterative potential location based on area requirement and mapping survey result. Following, each location alternative disassembly and examined their advantages and disadvantages in each aspect. Technical aspect analyze of land and territorial water technique. The approach that used in harbor location selection for this technique is weighting and assessment method in assessment matrix. The weighting value that used refers to harbor location selection in Makian bay. Meanwhile, for legality aspect, analyzed by policy review that relate to spatial area and location selection of harbor development. Based on minimum area demand analyze that 0.7 Ha for land facilities and 15.8 Ha for waters facilities. Refers to minimum area demand and layout spatial survey, four locations are selected for alternative points. After technical and legality aspect analyzed, then obtained second area chosen which located in Amed country, Purwakerti village.